Analytical Approaches for Assessing Curcumin and Nicotinamide Co-Encapsulated in Liposomal Formulation: UV Spectrophotometry and HPLC Validation - Fahdawi, Ali; Shalan, Naeem; Lafi, Zainab; Markab, Omar (Jordan Journal of Pharmaceutical Sciences, 2024)
Background: The study presents two distinct analytical methods tailored for the precise determination of curcumin (CUR) and nicotinamide (NIC) within liposomal formulations, addressing the needs of researchers and analysts in the biomedical and food supplement sectors. Method: UV spectrophotometry provides a swift and cost-effective solution for quantification, while High-Performance Liquid Chromatography (HPLC) offers enhanced specificity and sensitivity, particularly in complex matrices. Method validation, especially for HPLC, ensures reliability and suitability for rigorous analysis, advancing the field of Analytical Chemistry and strengthening development and quality assurance processes in the pharmaceutical and biotechnology industries. Results: The encapsulation efficiencies of CUR and NIC into liposomes, primarily composed of DPPC and CHO, were found to be 30% ± 6% and 80% ± 5%, respectively. The developed analytical methods using UV spectrophotometry and reverse-phase HPLC demonstrated robustness and efficiency, allowing for the simultaneous analysis of CUR and NIC with high specificity, accuracy, and precision. Validation according to ICH Q2 guidelines revealed excellent system suitability, linearity, and robustness, with relative standard deviation consistently below 2%. Stability studies over three weeks at 4°C showed minimal changes in liposomal characteristics, indicating good stability. Furthermore, release studies at 37°C demonstrated enhanced solubility and increased release of curcumin, suggesting the potential of the liposomal formulation for drug delivery applications. Conclusion: This study developed straightforward, time-efficient, and cost-effective analytical methods using UV spectrophotometry and reverse-phase HPLC to quantify CUR and NIC encapsulated in liposomal formulations.